2011
DOI: 10.1016/j.jval.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Análise de Custo-Efetividade da Sinvastatina versus Atorvastatina na Prevenção Secundária de Eventos Cardiovasculares no Sistema Único de Saúde Brasileiro

Abstract: This study is an important tool for public decision makers. The study can be used in the decision process of increasing cardiovascular disease treatment access with budgetary sustainability for Ministry of Health. In comparison to placebo, the results show that sinvastatin is a cost saving strategy while atorvastatin is not cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…So far, only one economic evaluation of statins has been performed in Brazil, where the cost-effectiveness of atorvastatin 10 mg and simvastatin 40 mg in secondary prevention were appraised 37 . The authors described dominance of simvastatin over both no treatment and atorvastatin, but the lack of a description of the details of the systematic review employed to determine the effectiveness of the treatments compromises the understanding of these results.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only one economic evaluation of statins has been performed in Brazil, where the cost-effectiveness of atorvastatin 10 mg and simvastatin 40 mg in secondary prevention were appraised 37 . The authors described dominance of simvastatin over both no treatment and atorvastatin, but the lack of a description of the details of the systematic review employed to determine the effectiveness of the treatments compromises the understanding of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que as estatinas possuem um importante efeito na redução de eventos cardiovasculares, uma vez que atuam reduzindo o LDL. No ano de 2009 o custo de tratamento com sinvastatina de 40 mg de um paciente era de R$36,50 por ano para o SUS, enquanto o custo com os cuidados de um paciente que sofreu um episódio agudo de AVC seria de R$ 2.994,94 (Araujo et al, 2011). Existem boas evidências em relação à eficácia da sinvastatina na prevenção da mortalidade no tratamento de dislipidemias (Brasil, 2020), entre os pacientes analisados, a sinvastatina foi a segunda estatina mais relatada, sendo uma alternativa eficiente e de custo mais baixo.…”
Section: Discussionunclassified
“…In 2011, a cost-effectiveness study evaluated the effect of simvastatin and atorvastatin compared to placebo in the perspective of the Brazilian Public Health System for the secondary prevention of cardiovascular events in dyslipidemic patients. The authors concluded that simvastatin alone was cost-effective (ARAUJO et al, 2011).…”
Section: Discussionmentioning
confidence: 99%